Heat-sealing preparation method of aluminized PE (polyethylene) film
By surface treatment of the PE base film and adding specific components, the problem of insufficient binding force during the heat sealing of aluminum-plated PE film is solved, and the heat sealing quality and mechanical properties are significantly improved.
Patent Information
- Application Number
- CN202411531824.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-11
AI Technical Summary
The aluminum-plated PE film has insufficient binding force and has defects such as bubbles and wrinkles during the heat sealing process, which affects the heat sealing quality.
By surface treatment of the PE base film, spraying with hydrogen peroxide solution and drying, the bonding strength between the PE film and the aluminum-plated film is improved. At the same time, ingredients such as acetyltributyl citrate (ATBC), polyethylene oxide (PEO) and polyacrylate were added to further enhance the binding force.
The mechanical properties and heat sealing quality of the aluminum-plated PE film are significantly improved, the adhesion between the aluminum-plated layer and the PE base film is enhanced, the peel strength is reduced, and the air-tightness and mechanical strength of the seal are improved.
Smart Images

Figure BDA0005110647900000201 
Figure BDA0005110647900000211
Abstract
Description
Technical Field
[0001] The invention provides a heat-sealing preparation method for an aluminum-plated PE film, and relates to the technical field of packaging material preparation. Background Art
[0002] Aluminized PE film (aluminized polyethylene film) is a composite material with an aluminum layer deposited on the surface of a polyethylene film. It is widely used in food packaging, medical packaging, and thermal insulation materials. Its excellent barrier properties and optical properties make it an important material in these fields. Heat sealing is one of the key steps in the processing of aluminized PE film, which directly affects the performance and quality of the final product. This article will provide a detailed technical introduction to the heat sealing preparation method of aluminized PE film, including the development of the technology, application prospects, existing mainstream technologies, defects and technical bottlenecks.
[0003] Early aluminized PE films were mainly made by vacuum evaporation technology to deposit an aluminum layer on the surface of the PE film. This technology was initially used to improve the barrier properties of packaging materials. With the development of technology, heat sealing technology has also gone through a process from simple heating and sealing to the use of higher precision equipment. In recent years, with the emergence of new materials and new technologies, the heat sealing technology of aluminized PE films has been significantly improved. For example, the application of laser heat sealing technology and ultrasonic heat sealing technology has improved the accuracy and efficiency of heat sealing. At the same time, the surface treatment technology of the film, such as plasma treatment and chemical plating, has also further improved the bonding strength between the aluminized film and the PE film.
[0004] Aluminized PE film is widely used in food packaging. Its excellent barrier properties can effectively extend the shelf life of food and maintain the freshness and nutritional content of food. In the pharmaceutical industry, aluminized PE film can be used to protect medicines from moisture and light, ensuring the stability and effectiveness of medicines. Aluminized PE film has good reflectivity and heat insulation, so it is also used in thermal insulation materials, such as building insulation materials and automotive insulation materials. In some special applications, such as electronic product packaging, the anti-electromagnetic interference characteristics of aluminized PE film also have certain application prospects.
[0005] Vacuum evaporation technology is the most commonly used method in the production of aluminized PE film. Aluminum is evaporated and deposited on the surface of the PE film under a vacuum environment to form a uniform aluminum layer. This technology has a high deposition rate and film uniformity, but it has high requirements for equipment. Laser heat sealing technology uses a laser beam to accurately control the heating area to achieve high-precision heat sealing of aluminized PE film. This technology can effectively reduce the errors generated in the traditional heat sealing process and improve the sealing strength and consistency. Ultrasonic heat sealing technology uses the heat generated by ultrasonic vibration for sealing, and has the advantages of fast heating speed and low energy consumption. This technology is suitable for the sealing of thin films and multi-layer films, but it has high requirements for equipment adjustment and maintenance. Plasma treatment technology improves the adhesion of the film by changing the chemical properties of the film surface.
[0006] The bonding strength between aluminized film and PE film is one of the key factors affecting the quality of heat sealing. Current technology still faces challenges in improving bonding strength. The main reasons include: Insufficient surface treatment: Although plasma treatment and chemical treatment can increase the surface energy, uneven treatment effects may lead to unstable bonding. Aluminum layer thickness problem: Too thin an aluminum layer may lead to insufficient adhesion, while too thick may affect the flexibility and processing performance of the film. Imprecise control of heat sealing parameters: Imprecise control of temperature, pressure and time during the heat sealing process will lead to insufficient sealing strength. Defects in the heat sealing process: Some defects that may occur during the heat sealing process include: Bubbles and wrinkles: Uneven heating or insufficient pressure may cause bubbles or wrinkles, affecting the quality of heat sealing. Uneven sealing: Uneven sealing may occur due to improper equipment adjustment or uneven materials.
[0007] The heat-sealing preparation methods of aluminized PE films have made significant progress in the past few decades. Modern technologies such as laser heat sealing, ultrasonic heat sealing and plasma treatment have improved the heat sealing quality and efficiency. However, insufficient bonding and defects in the heat sealing process remain technical bottlenecks. Future research should focus on improving surface treatment technology, optimizing heat sealing parameter control and reducing equipment costs to further improve the performance and application range of aluminized PE films. Summary of the invention
[0008] In order to solve the above problems, the present invention provides a heat-sealing preparation method of aluminum-plated PE film, and the specific scheme is as follows:
[0009] A heat-sealing preparation method for an aluminum-plated PE film comprises the following steps:
[0010] S1. Take all the components in the PE film and mix them in a high-speed mixer to obtain a mixed material;
[0011] S2, the obtained mixture is melted by a twin-screw extruder, and a three-layer co-extrusion die is used for co-extrusion molding to obtain a three-layer sheet, and the obtained three-layer sheet is blown through an annular die head, and the obtained film is immediately cooled to room temperature by a cooling roller after film blowing to obtain a PE base film;
[0012] S3, spraying the obtained PE base film surface with hydrogen peroxide solution to perform surface treatment, and rinsing the treated surface with deionized water and drying after the treatment to obtain a surface-treated PE base film;
[0013] S4. Prepare an aluminum-plated layer on the surface of the substrate, and heat-seal and bond the aluminum-plated layer to the obtained surface-treated PE base film to obtain an aluminum-plated PE film, wherein the aluminum-plated layer is on the surface-treated side of the surface-treated PE base film.
[0014] Preferably, the aluminized PE film obtained in S4 is slit and rolled, and packaged and stored for later use.
[0015] Preferably, the three-layer sheet described in S2 includes a middle layer and two surface layers respectively located on both sides of the middle layer, wherein the middle layer includes the following components: polypropylene (PP), ethylene / methacrylic acid copolymer (EMA), low-density polyethylene (LDPE), ethylene-acrylic acid copolymer (EAA), polyurethane, polyamide, triethoxyethylsilane, calcium stearate, antioxidant, and light stabilizer; the surface layer includes the following components: polypropylene (PP), ethylene / methacrylic acid copolymer (EMA), low-density polyethylene (LDPE), ethylene-acrylic acid copolymer (EAA), acetyl tributyl citrate (ATBC), polyethylene oxide (PEO), polyacrylate, polyurethane, polyamide, triethoxyethylsilane, calcium stearate, antioxidant, and light stabilizer.
[0016] Preferably, the mixing in S1 is carried out at room temperature, with a high-speed mixer speed of 800-1000 rpm and a mixing time of 15-20 min.
[0017] Preferably, the melting temperature of S2 is 180-200°C, the speed of the twin-screw extruder is 150-180rpm; the temperature of the co-extrusion mold is 200-220°C; the thickness of the obtained three-layer sheet is 0.3-1.0mm; the film blowing temperature is 180-190°C, the air pressure is 0.5-0.8MPa, the blowing ratio is (4-5):1, and the thickness of the obtained PE base film is 20-80μm.
[0018] Preferably, the concentration of the hydrogen peroxide solution in S3 is 0.1-1.0% (w / v).
[0019] Preferably, the surface treatment in S3 is carried out at a temperature of 30-50°C for 1-3 min; and the drying is carried out by hot air drying at a temperature of 30-40°C.
[0020] Preferably, the substrate in S4 comprises a PET film, the thickness of the aluminum coating layer is 20-60 nm; the heat sealing temperature is 120-150° C., the pressure is 0.2-0.4 MPa, and the heat sealing time is 0.5-2.0 s.
[0021] Preferably, the components in the surface layer are as follows by mass:
[0022] Polypropylene (PP) 15-20 parts,
[0023] Ethylene / methacrylic acid copolymer (EMA) 25-35 parts,
[0024] Low density polyethylene (LDPE) 20-30 parts,
[0025] Ethylene acrylic acid copolymer (EAA) 5-10 parts,
[0026] 1-3 parts of acetyl tributyl citrate (ATBC),
[0027] Polyethylene oxide (PEO) 1-3 parts,
[0028] Polyacrylate 1-3 parts,
[0029] Polyurethane (PU) 3-7 parts,
[0030] Polyamide 2-5 parts,
[0031] 0.5-2 parts of triethoxyethylsilane,
[0032] Calcium stearate 1-3 parts,
[0033] 1-3 parts of antioxidant,
[0034] Light stabilizer 1-3 parts.
[0035] Preferably, the components in the middle layer are as follows, by weight: 15-20 parts of polypropylene (PP),
[0036] Ethylene / methacrylic acid copolymer (EMA) 25-35 parts, low-density polyethylene (LDPE) 20-30 parts,
[0037] Ethylene acrylic acid copolymer (EAA) 5-10 parts, polyurethane (PU) 3-7 parts,
[0038] Polyamide 2-5 parts,
[0039] 0.5-2 parts of triethoxyethylsilane,
[0040] Calcium stearate 1-3 parts,
[0041] 1-3 parts of antioxidant,
[0042] Light stabilizer 1-3 parts.
[0043] The beneficial effects of the present invention are as follows:
[0044] The present invention effectively increases the bonding strength between the PE film and the aluminized film by surface treatment of the PE base film; in addition, acetyl tributyl citrate (ATBC), polyethylene oxide (PEO) and polyacrylate added to the PE base film provided by the present invention further increase the bonding strength between the PE film and the aluminized film, so that the obtained aluminized PE film has better mechanical properties. DETAILED DESCRIPTION
[0045] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0046] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0047] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified. Ethylene / methacrylic acid copolymer (EMA) can be AX8840 from Dongguan Shangpin New Material Technology Co., Ltd.
[0048] Example 1 Preparation of heat seal of aluminum-plated PE film:
[0049] The three-layer sheet in the preparation process includes a middle layer and two surface layers located on both sides of the middle layer, wherein the components in the surface layer are calculated by weight as follows:
[0050] Polypropylene (PP) 15-20 parts,
[0051] Ethylene / methacrylic acid copolymer (EMA) 25-35 parts,
[0052] Low density polyethylene (LDPE) 20-30 parts,
[0053] Ethylene acrylic acid copolymer (EAA) 5-10 parts,
[0054] 1-3 parts of acetyl tributyl citrate (ATBC),
[0055] Polyethylene oxide (PEO) 1-3 parts,
[0056] Polyacrylate 1-3 parts,
[0057] Polyurethane (PU) 3-7 parts,
[0058] Polyamide 2-5 parts,
[0059] 0.5-2 parts of triethoxyethylsilane,
[0060] Calcium stearate 1-3 parts,
[0061] 1-3 parts of antioxidant,
[0062] 1-3 parts of light stabilizer;
[0063] The components in the middle layer are calculated by weight:
[0064] Polypropylene (PP) 15-20 parts,
[0065] Ethylene / methacrylic acid copolymer (EMA) 25-35 parts,
[0066] Low density polyethylene (LDPE) 20-30 parts,
[0067] Ethylene acrylic acid copolymer (EAA) 5-10 parts,
[0068] Polyurethane (PU) 3-7 parts,
[0069] Polyamide 2-5 parts,
[0070] 0.5-2 parts of triethoxyethylsilane,
[0071] Calcium stearate 1-3 parts,
[0072] 1-3 parts of antioxidant,
[0073] Light stabilizer 1-3 parts.
[0074] Preparation process:
[0075] S1. Take all the components in the PE film and mix them in a high-speed mixer to obtain a mixed material;
[0076] S2, the obtained mixture is melted by a twin-screw extruder, and a three-layer co-extrusion die is used for co-extrusion molding to obtain a three-layer sheet, and the obtained three-layer sheet is blown through an annular die head, and the obtained film is immediately cooled to room temperature by a cooling roller after film blowing to obtain a PE base film;
[0077] S3, spraying the obtained PE base film surface with hydrogen peroxide solution to perform surface treatment, and rinsing the treated surface with deionized water and drying after the treatment to obtain a surface-treated PE base film;
[0078] S4. Prepare an aluminum-plated layer on the surface of the substrate, and heat-seal and bond the aluminum-plated layer to the obtained surface-treated PE base film to obtain an aluminum-plated PE film, wherein the aluminum-plated layer is on the surface-treated side of the surface-treated PE base film.
[0079] The aluminized PE film obtained in S4 is slit and rolled, and packaged and stored for later use.
[0080] The mixing described in S1 is carried out at room temperature, with a high-speed mixer speed of 800-1000 rpm and a mixing time of 15-20 min.
[0081] S2 The melting temperature is 180-200°C, the speed of the twin-screw extruder is 150-180rpm; the temperature of the co-extrusion mold is 200-220°C; the thickness of the obtained three-layer sheet is 0.3-1.0mm; the film blowing temperature is 180-190°C, the air pressure is 0.5-0.8MPa, the blowing ratio is (4-5):1, and the thickness of the obtained PE base film is 20-80μm.
[0082] The concentration of the hydrogen peroxide solution in S3 is 0.1-1.0% (w / v).
[0083] The surface treatment in S3 is carried out at a temperature of 30-50°C for 1-3 minutes; the drying is carried out by hot air drying at a temperature of 30-40°C.
[0084] S4: the substrate comprises a PET film, the thickness of the aluminum coating is 20-60 nm; the heat sealing temperature is 120-150° C., the pressure is 0.2-0.4 MPa, and the heat sealing time is 0.5-2.0 s.
[0085] Example 1 Preparation of heat-sealed aluminum-plated PE film:
[0086] The three-layer sheet in the preparation process includes a middle layer and two surface layers located on both sides of the middle layer, wherein the components in the surface layer are calculated by weight as follows:
[0087] Polypropylene (PP) 20 parts,
[0088] Ethylene / methacrylic acid copolymer (EMA) 25 parts,
[0089] 20 parts of low-density polyethylene (LDPE),
[0090] 5 parts of ethylene-acrylic acid copolymer (EAA),
[0091] 1 part of acetyl tributyl citrate (ATBC),
[0092] 1 part of polyethylene oxide (PEO),
[0093] Polyacrylate 1 part,
[0094] Polyurethane (PU) 3 parts,
[0095] Polyamide 2 parts,
[0096] 0.5 parts of triethoxyethylsilane,
[0097] 1 part calcium stearate,
[0098] 1 part antioxidant,
[0099] 1 part of light stabilizer;
[0100] The components in the middle layer are calculated by weight: 20 parts of polypropylene (PP),
[0101] 25 parts of ethylene / methacrylic acid copolymer (EMA), 20 parts of low-density polyethylene (LDPE), 5 parts of ethylene-acrylic acid copolymer (EAA), 3 parts of polyurethane (PU),
[0102] Polyamide 2 parts,
[0103] 0.5 parts of triethoxyethylsilane,
[0104] 1 part calcium stearate,
[0105] 1 part antioxidant,
[0106] 1 part of light stabilizer.
[0107] Preparation process:
[0108] S1. Take all the components in the PE film and mix them in a high-speed mixer to obtain a mixed material;
[0109] S2, the obtained mixture is melted by a twin-screw extruder, and a three-layer co-extrusion die is used for co-extrusion molding to obtain a three-layer sheet, and the obtained three-layer sheet is blown through an annular die head, and the obtained film is immediately cooled to room temperature by a cooling roller after film blowing to obtain a PE base film;
[0110] S3, spraying the obtained PE base film surface with hydrogen peroxide solution to perform surface treatment, and rinsing the treated surface with deionized water and drying after the treatment to obtain a surface-treated PE base film;
[0111] S4. Prepare an aluminum-plated layer on the surface of the substrate, and heat-seal and bond the aluminum-plated layer to the obtained surface-treated PE base film to obtain an aluminum-plated PE film, wherein the aluminum-plated layer is on the surface-treated side of the surface-treated PE base film.
[0112] The aluminized PE film obtained in S4 is slit and rolled, and packaged and stored for later use.
[0113] The mixing described in S1 was carried out at room temperature, with a high-speed mixer speed of 800 rpm and a mixing time of 20 min.
[0114] The melting temperature of S2 is 180°C, and the speed of the twin-screw extruder is 150rpm; the temperature of the co-extrusion mold is 200°C; the thickness of the obtained three-layer sheet is 0.3mm; the temperature of the blown film is 180°C, the air pressure is 0.5MPa, the blowing ratio is 4:1, and the thickness of the obtained PE base film is 75μm.
[0115] The concentration of the hydrogen peroxide solution in S3 is 0.5% (w / v).
[0116] The surface treatment in S3 is carried out at a temperature of 50°C for 1 min. The drying is carried out by hot air drying at a temperature of 40°C.
[0117] S4: the substrate comprises a PET film, the thickness of the aluminum coating layer is 50 nm; the heat sealing temperature is 150° C., the pressure is 0.2 MPa, and the heat sealing time is 1.0 s.
[0118] Example 2 Preparation of heat-sealed aluminum-plated PE film (the difference from Example 1 is that the PP content in the formula is reduced and other components are increased):
[0119] The three-layer sheet in the preparation process includes a middle layer and two surface layers located on both sides of the middle layer, wherein the components in the surface layer are calculated by weight as follows:
[0120] Polypropylene (PP) 20 parts,
[0121] Ethylene / methacrylic acid copolymer (EMA) 35 parts,
[0122] 30 parts of low-density polyethylene (LDPE),
[0123] 10 parts of ethylene-acrylic acid copolymer (EAA),
[0124] 3 parts of acetyl tributyl citrate (ATBC),
[0125] 3 parts of polyethylene oxide (PEO),
[0126] Polyacrylate 3 parts,
[0127] Polyurethane (PU) 7 parts,
[0128] Polyamide 5 parts,
[0129] 2 parts of triethoxyethylsilane,
[0130] Calcium stearate 3 parts,
[0131] 3 parts of antioxidant,
[0132] 1-3 parts of light stabilizer;
[0133] The components in the middle layer are calculated by weight:
[0134] Polypropylene (PP) 20 parts,
[0135] Ethylene / methacrylic acid copolymer (EMA) 35 parts,
[0136] 30 parts of low-density polyethylene (LDPE),
[0137] 10 parts of ethylene-acrylic acid copolymer (EAA),
[0138] Polyurethane (PU) 7 parts,
[0139] Polyamide 5 parts,
[0140] 2 parts of triethoxyethylsilane,
[0141] Calcium stearate 3 parts,
[0142] 3 parts of antioxidant,
[0143] 3 parts of light stabilizer.
[0144] Preparation process:
[0145] S1. Take all the components in the PE film and mix them in a high-speed mixer to obtain a mixed material;
[0146] S2, the obtained mixture is melted by a twin-screw extruder, and a three-layer co-extrusion die is used for co-extrusion molding to obtain a three-layer sheet, and the obtained three-layer sheet is blown through an annular die head, and the obtained film is immediately cooled to room temperature by a cooling roller after film blowing to obtain a PE base film;
[0147] S3, spraying the obtained PE base film surface with hydrogen peroxide solution to perform surface treatment, and rinsing the treated surface with deionized water and drying after the treatment to obtain a surface-treated PE base film;
[0148] S4. Prepare an aluminum-plated layer on the surface of the substrate, and heat-seal and bond the aluminum-plated layer to the obtained surface-treated PE base film to obtain an aluminum-plated PE film, wherein the aluminum-plated layer is on the surface-treated side of the surface-treated PE base film.
[0149] The aluminized PE film obtained in S4 is slit and rolled, and packaged and stored for later use.
[0150] The mixing described in S1 was carried out at room temperature, with a high-speed mixer speed of 800 rpm and a mixing time of 20 min.
[0151] The melting temperature of S2 is 180°C, and the speed of the twin-screw extruder is 150rpm; the temperature of the co-extrusion mold is 200°C; the thickness of the obtained three-layer sheet is 0.3mm; the temperature of the blown film is 180°C, the air pressure is 0.5MPa, the blowing ratio is 4:1, and the thickness of the obtained PE base film is 75μm.
[0152] The concentration of the hydrogen peroxide solution in S3 is 0.5% (w / v).
[0153] The surface treatment in S3 is carried out at a temperature of 50°C for 1 min. The drying is carried out by hot air drying at a temperature of 40°C.
[0154] S4: the substrate comprises a PET film, the thickness of the aluminum coating layer is 50 nm; the heat sealing temperature is 150° C., the pressure is 0.2 MPa, and the heat sealing time is 1.0 s.
[0155] Example 3 Preparation of heat-sealed aluminum-plated PE film (the difference from Example 1 is that acetyl tributyl citrate is increased in the formula):
[0156] The three-layer sheet in the preparation process includes a middle layer and two surface layers located on both sides of the middle layer, wherein the components in the surface layer are calculated by weight as follows:
[0157] Polypropylene (PP) 20 parts,
[0158] Ethylene / methacrylic acid copolymer (EMA) 25 parts,
[0159] 20 parts of low-density polyethylene (LDPE),
[0160] 5 parts of ethylene-acrylic acid copolymer (EAA),
[0161] 3 parts of acetyl tributyl citrate (ATBC), 1 part of polyethylene oxide (PEO),
[0162] Polyacrylate 1 part,
[0163] Polyurethane (PU) 3 parts,
[0164] Polyamide 2 parts,
[0165] 0.5 parts of triethoxyethylsilane,
[0166] 1 part calcium stearate,
[0167] 1 part antioxidant,
[0168] 1 part of light stabilizer;
[0169] The components in the middle layer are calculated by weight: 20 parts of polypropylene (PP),
[0170] 25 parts of ethylene / methacrylic acid copolymer (EMA), 20 parts of low-density polyethylene (LDPE), 5 parts of ethylene-acrylic acid copolymer (EAA), 3 parts of polyurethane (PU),
[0171] Polyamide 2 parts,
[0172] 0.5 parts of triethoxyethylsilane,
[0173] 1 part calcium stearate,
[0174] 1 part antioxidant,
[0175] 1 part of light stabilizer.
[0176] Preparation process:
[0177] S1. Take all the components in the PE film and mix them in a high-speed mixer to obtain a mixed material;
[0178] S2, the obtained mixture is melted by a twin-screw extruder, and a three-layer co-extrusion die is used for co-extrusion molding to obtain a three-layer sheet, and the obtained three-layer sheet is blown through an annular die head, and the obtained film is immediately cooled to room temperature by a cooling roller after film blowing to obtain a PE base film;
[0179] S3, spraying the obtained PE base film surface with hydrogen peroxide solution to perform surface treatment, and rinsing the treated surface with deionized water and drying after the treatment to obtain a surface-treated PE base film;
[0180] S4. Prepare an aluminum-plated layer on the surface of the substrate, and heat-seal and bond the aluminum-plated layer to the obtained surface-treated PE base film to obtain an aluminum-plated PE film, wherein the aluminum-plated layer is on the surface-treated side of the surface-treated PE base film.
[0181] The aluminized PE film obtained in S4 is slit and rolled, and packaged and stored for later use.
[0182] The mixing described in S1 was carried out at room temperature, with a high-speed mixer speed of 800 rpm and a mixing time of 20 min.
[0183] The melting temperature of S2 is 180°C, and the speed of the twin-screw extruder is 150rpm; the temperature of the co-extrusion mold is 200°C; the thickness of the obtained three-layer sheet is 0.3mm; the temperature of the blown film is 180°C, the air pressure is 0.5MPa, the blowing ratio is 4:1, and the thickness of the obtained PE base film is 75μm.
[0184] The concentration of the hydrogen peroxide solution in S3 is 0.5% (w / v).
[0185] The surface treatment in S3 is carried out at a temperature of 50°C for 1 min. The drying is carried out by hot air drying at a temperature of 40°C.
[0186] S4: the substrate comprises a PET film, the thickness of the aluminum coating layer is 50 nm; the heat sealing temperature is 150° C., the pressure is 0.2 MPa, and the heat sealing time is 1.0 s.
[0187] Example 4 Preparation of heat-sealed aluminum-plated PE film (the difference from Example 1 is that the content of polyethylene oxide and polyacrylate in the formula is increased):
[0188] The three-layer sheet in the preparation process includes a middle layer and two surface layers located on both sides of the middle layer, wherein the components in the surface layer are calculated by weight as follows:
[0189] Polypropylene (PP) 20 parts,
[0190] Ethylene / methacrylic acid copolymer (EMA) 25 parts,
[0191] 20 parts of low-density polyethylene (LDPE),
[0192] 5 parts of ethylene-acrylic acid copolymer (EAA),
[0193] 1 part of acetyl tributyl citrate (ATBC),
[0194] 3 parts of polyethylene oxide (PEO),
[0195] Polyacrylate 3 parts,
[0196] Polyurethane (PU) 3 parts,
[0197] Polyamide 2 parts,
[0198] 0.5 parts of triethoxyethylsilane,
[0199] 1 part calcium stearate,
[0200] 1 part antioxidant,
[0201] 1 part of light stabilizer;
[0202] The components in the middle layer are calculated by weight:
[0203] Polypropylene (PP) 20 parts,
[0204] Ethylene / methacrylic acid copolymer (EMA) 25 parts,
[0205] 20 parts of low-density polyethylene (LDPE),
[0206] 5 parts of ethylene-acrylic acid copolymer (EAA),
[0207] Polyurethane (PU) 3 parts,
[0208] Polyamide 2 parts,
[0209] 0.5 parts of triethoxyethylsilane,
[0210] 1 part calcium stearate,
[0211] 1 part antioxidant,
[0212] 1 part of light stabilizer.
[0213] Preparation process:
[0214] S1. Take all the components in the PE film and mix them in a high-speed mixer to obtain a mixed material;
[0215] S2, the obtained mixture is melted by a twin-screw extruder, and a three-layer co-extrusion die is used for co-extrusion molding to obtain a three-layer sheet, and the obtained three-layer sheet is blown through an annular die head, and the obtained film is immediately cooled to room temperature by a cooling roller after film blowing to obtain a PE base film;
[0216] S3, spraying the obtained PE base film surface with hydrogen peroxide solution to perform surface treatment, and rinsing the treated surface with deionized water and drying after the treatment to obtain a surface-treated PE base film;
[0217] S4. Prepare an aluminum-plated layer on the surface of the substrate, and heat-seal and bond the aluminum-plated layer to the obtained surface-treated PE base film to obtain an aluminum-plated PE film, wherein the aluminum-plated layer is on the surface-treated side of the surface-treated PE base film.
[0218] The aluminized PE film obtained in S4 is slit and rolled, and packaged and stored for later use.
[0219] The mixing described in S1 was carried out at room temperature, with a high-speed mixer speed of 800 rpm and a mixing time of 20 min.
[0220] The melting temperature of S2 is 180°C, and the speed of the twin-screw extruder is 150rpm; the temperature of the co-extrusion mold is 200°C; the thickness of the obtained three-layer sheet is 0.3mm; the temperature of the blown film is 180°C, the air pressure is 0.5MPa, the blowing ratio is 4:1, and the thickness of the obtained PE base film is 75μm.
[0221] The concentration of the hydrogen peroxide solution in S3 is 0.5% (w / v).
[0222] The surface treatment in S3 is carried out at a temperature of 50°C for 1 min. The drying is carried out by hot air drying at a temperature of 40°C.
[0223] S4: the substrate comprises a PET film, the thickness of the aluminum coating layer is 50 nm; the heat sealing temperature is 150° C., the pressure is 0.2 MPa, and the heat sealing time is 1.0 s.
[0224] The difference between Comparative Example 1 and Example 1 is that acetyl tributyl citrate (ATBC) is not included in the surface layer formula.
[0225] The difference between Comparative Example 2 and Example 1 is that the surface layer formula does not include polyethylene oxide (PEO).
[0226] The difference between Comparative Example 3 and Example 1 is that the surface layer formula does not include polyacrylate.
[0227] The difference between Comparative Example 4 and Example 1 is that the surface layer formula does not include polyethylene oxide (PEO) and polyacrylate.
[0228] The difference between Comparative Example 5 and Example 1 is that the surface layer formula adopts the middle layer formula (still maintaining a three-layer structure).
[0229] The difference between Comparative Example 6 and Example 1 is that a single-layer structure is adopted and the formula adopts a surface layer formula.
[0230] The difference between Comparative Example 7 and Example 1 is that the treatment of S3 is not performed.
[0231] The difference between Comparative Example 8 and Example 1 is that S3 is replaced by corona surface treatment: the surface layer on one side is subjected to corona treatment to make its surface tension reach more than 40 dynes.
[0232] The membrane materials obtained in the above examples and comparative examples were tested using the following standards:
[0233] 1. Thickness measurement: GB / T 6672-2001, within the film sample range of 100 mm in length and width, the thickness gauge measures the thickness at different positions (10 different points) of the sample and takes the average value.
[0234] 2. Tensile performance test: GB / T 1040.3-2006, use a tensile testing machine to test the maximum tensile force, tensile strength and elongation at break of the sample.
[0235] 3. Barrier performance test (oxygen permeability and water vapor permeability): GB / T 1038-2000 (oxygen permeability), GB / T1037-1988 (water vapor permeability), test sample specifications: round samples with a diameter of 10 cm, use a gas permeability tester to measure the oxygen and water vapor permeability of the sample.
[0236] 4. Friction coefficient test: GB 10006-1988, test sample specifications: samples with a length and width of 200 mm, use a friction coefficient meter to measure the static friction coefficient and dynamic friction coefficient between the sample surface and another standard surface.
[0237] 5. Peel strength test: GB / T 2790-1995, test sample specifications: film sample with a width of 15 mm and a length of 100 mm, using a peel tester, test the peel strength between the film and the aluminum coating at a peel angle of 180°. The above test results are shown in Table 1.
[0238] Table 1 Sample test results
[0239]
[0240]
[0241] From the above results, it can be seen that acetyl tributyl citrate (ATBC), polyethylene oxide (PEO), and polyacrylate are added to the film formula, and the PE base film is treated with hydrogen peroxide and then combined with the aluminum-plated film layer by heat sealing. The peel strength is the highest. When any one of acetyl tributyl citrate (ATBC), polyethylene oxide (PEO), and polyacrylate is removed, or no hydrogen peroxide treatment is performed, the peel strength is greatly reduced, and corona treatment cannot replace hydrogen peroxide treatment to bring the same effect. ATBC is a plasticizer, which may increase the flexibility and plasticity of the film in the polymer base film. Hydrogen peroxide treatment may cause microstructural changes or oxidation reactions between the film surface and ATBC, causing changes in the surface activity or affinity of ATBC, further promoting the adhesion of the aluminum-plated layer. PEO is a hydrophilic polymer that easily forms hydrogen bonds in its molecular structure. Hydrogen peroxide treatment may introduce additional polar groups or active centers, making it easier for PEO to physically or chemically interact with these active sites, thereby increasing interfacial adhesion. Polyacrylates are polar and may produce certain surface reactions during hydrogen peroxide treatment, so that these polymers form stronger adhesion in the interface area. However, in the present invention, the greater role of polyacrylate is to increase the compatibility of PEO with the system as a whole, and to avoid the presence of PEO causing a reduction in other mechanical properties. When ATBC, PEO, and polyacrylate are present at the same time, hydrogen peroxide treatment may induce a certain synergistic effect, and the polar groups produced during the oxidation process may interact with these additives to form a more stable interface layer, thereby enhancing the bonding force between the PE base film and the aluminum coating; in addition, hydrogen peroxide treatment may induce a certain form of crosslinking or copolymerization reaction on the film surface, so that these additives (such as ATBC, PEO, polyacrylate) form a certain chemical bond with the base film or the aluminum coating, thereby greatly improving the peel strength. Corona treatment mainly excites the molecules on the surface of the film through a high-energy electric field, produces a small amount of polar groups (such as carbonyl, hydroxyl), thereby increasing the surface energy, but its effect is relatively weak and cannot be compared with the treatment effect of a strong oxidant such as hydrogen peroxide. Corona treatment does not initiate a similar chemical reaction or cross-linking process and therefore does not significantly enhance the adhesion of the film surface as hydrogen peroxide treatment does.
[0242] In addition, the aluminized PE film prepared by the present invention exhibits a remarkable characteristic: its aluminized surface can be directly heat-sealed with the PE film on the other side. This characteristic is achieved through a carefully designed multi-layer structure and material selection, which ensures good adhesion and compatibility between the aluminized layer and the PE base film. During the preparation process, the aluminized layer is uniformly applied to the PE base film that has undergone a special surface treatment. The surface treatment enhances the surface energy of the PE film and improves its adhesion to the metal aluminum layer. This enhanced interfacial force ensures the structural integrity and sealing of the aluminized layer during the heat sealing process. The heat sealing process itself is carried out under controlled temperature and pressure, and these conditions are precisely set to adapt to the melting point of the PE film and the thermal stability of the aluminized layer. In addition, the PE film material used is specially selected to have good heat sealing properties, which means that when heated, the layers of the PE film can be effectively fused without damaging or degrading the aluminized layer. This direct heat sealing ability greatly simplifies the packaging process, improves production efficiency, and ensures the airtightness and mechanical strength of the seal, which is crucial for food packaging and storage.
[0243] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
[0244] The present invention and its implementation methods are described above, which is not restrictive and is only one of the implementation methods of the present invention. The actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A heat-sealing preparation method for an aluminum-plated PE film, characterized in that: The following steps are involved: S1. Take all the components in the PE film and mix them in a high-speed mixer to obtain a mixed material; S2, the obtained mixture is melted by a twin-screw extruder, and a three-layer co-extrusion die is used for co-extrusion molding to obtain a three-layer sheet, and the obtained three-layer sheet is blown through an annular die head, and the obtained film is immediately cooled to room temperature by a cooling roller after film blowing to obtain a PE base film; S3, spraying the obtained PE base film surface with hydrogen peroxide solution to perform surface treatment, and rinsing the treated surface with deionized water and drying after the treatment to obtain a surface-treated PE base film; S4. Prepare an aluminum-plated layer on the surface of the substrate, and heat-seal and bond the aluminum-plated layer to the obtained surface-treated PE base film to obtain an aluminum-plated PE film, wherein the aluminum-plated layer is on the surface-treated side of the surface-treated PE base film.
2. The heat-sealing preparation method of aluminized PE film according to claim 1, characterized in that: S2 The three-layer sheet comprises a middle layer and two surface layers respectively located on both sides of the middle layer, wherein the middle layer comprises the following components: polypropylene (PP), ethylene / methacrylic acid copolymer (EMA), low-density polyethylene (LDPE), ethylene-acrylic acid copolymer (EAA), polyurethane, polyamide, triethoxyethylsilane, calcium stearate, antioxidant, and light stabilizer; the surface layer comprises the following components: polypropylene (PP), ethylene / methacrylic acid copolymer (EMA), low-density polyethylene (LDPE), ethylene-acrylic acid copolymer (EAA), acetyl tributyl citrate (ATBC), polyethylene oxide (PEO), polyacrylate, polyurethane, polyamide, triethoxyethylsilane, calcium stearate, antioxidant, and light stabilizer.
3. The heat-sealing preparation method of aluminized PE film according to claim 1, characterized in that: The mixing described in S1 is carried out at room temperature, with a high-speed mixer speed of 800-1000 rpm and a mixing time of 15-20 min.
4. The heat-sealing preparation method of aluminized PE film according to claim 1, characterized in that: S2 The melting temperature is 180-200°C, the speed of the twin-screw extruder is 150-180rpm; the co-extrusion die temperature is 200-220°C.
5. The heat-sealing preparation method of aluminized PE film according to claim 1, characterized in that: The thickness of the three-layer sheet obtained in S2 is 0.3-1.0 mm; the film blowing temperature is 180-190° C., the air pressure is 0.5-0.8 MPa, the blowing ratio is (4-5):1, and the thickness of the obtained PE base film is 20-80 μm.
6. The heat-sealing preparation method of aluminized PE film according to claim 1, characterized in that: The concentration of the hydrogen peroxide solution in S3 is 0.1-1.0% (w / v).
7. The heat-sealing preparation method of aluminum-plated PE film according to claim 1, characterized in that: The surface treatment in S3 is carried out at a temperature of 30-50°C for 1-3 minutes; the drying is carried out by hot air drying at a temperature of 30-40°C.
8. The heat-sealing preparation method of aluminum-plated PE film according to claim 1, characterized in that: S4: the substrate comprises a PET film, the thickness of the aluminum coating is 20-60 nm; the heat sealing temperature is 120-150° C., the pressure is 0.2-0.4 MPa, and the heat sealing time is 0.5-2.0 s.
9. The heat-sealing preparation method of aluminum-plated PE film according to claim 2, characterized in that: The components in the surface layer are calculated by weight: Polypropylene (PP) 15-20 parts, Ethylene / methacrylic acid copolymer (EMA) 25-35 parts, Low density polyethylene (LDPE) 20-30 parts, Ethylene acrylic acid copolymer (EAA) 5-10 parts, 1-3 parts of acetyl tributyl citrate (ATBC), Polyethylene oxide (PEO) 1-3 parts, Polyacrylate 1-3 parts, Polyurethane (PU) 3-7 parts, Polyamide 2-5 parts, 0.5-2 parts of triethoxyethylsilane, Calcium stearate 1-3 parts, 1-3 parts of antioxidant, Light stabilizer 1-3 parts.
10. The heat-sealing preparation method of aluminum-plated PE film according to claim 2, characterized in that: The components in the intermediate layer are calculated by weight: Polypropylene (PP) 15-20 parts, Ethylene / methacrylic acid copolymer (EMA) 25-35 parts, Low density polyethylene (LDPE) 20-30 parts, Ethylene acrylic acid copolymer (EAA) 5-10 parts, Polyurethane (PU) 3-7 parts, Polyamide 2-5 parts, 0.5-2 parts of triethoxyethylsilane, Calcium stearate 1-3 parts, 1-3 parts of antioxidant, Light stabilizer 1-3 parts.